2022
DOI: 10.1091/mbc.e21-10-0517-t
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 increases microtubules and disrupts centriolar satellite localization

Abstract: This article explores why elevated pericentrin in trisomy 21 negatively impacts primary cilia. It is found that elevated pericentrin produces more pericentrosomal puncta that associate with and increase microtubules. Elevated pericentrin and microtubules mislocalize centriolar satellites in a pericentrosomal crowd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…PCNT is encoded on HSA21 resulting in 1.5-fold increased expression in trisomy 21 ( Galati et al, 2018 ; McCurdy et al, 2022 ). We previously showed that elevated PCNT protein is sufficient for decreased ciliation in trisomy 21 cells ( Galati et al, 2018 ; McCurdy et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PCNT is encoded on HSA21 resulting in 1.5-fold increased expression in trisomy 21 ( Galati et al, 2018 ; McCurdy et al, 2022 ). We previously showed that elevated PCNT protein is sufficient for decreased ciliation in trisomy 21 cells ( Galati et al, 2018 ; McCurdy et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…PCNT is encoded on HSA21 resulting in 1.5-fold increased expression in trisomy 21 ( Galati et al, 2018 ; McCurdy et al, 2022 ). We previously showed that elevated PCNT protein is sufficient for decreased ciliation in trisomy 21 cells ( Galati et al, 2018 ; McCurdy et al, 2022 ). Whereas PCNT normally organizes microtubules emanating from centrosomes, elevated PCNT has three major consequences in trisomy 21 cells ( Figure 1A ): (1) PCNT increases microtubule density around the centrosome; (2) PCNT forms large protein aggregates along these microtubules; and (3) PCNT resides at the ends of cytoplasmic microtubules that are disconnected from the centrosome ( Galati et al, 2018 ; McCurdy et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations